Venovenous extracorporeal membrane oxygenation in patients with acute covid-19 associated respiratory failure: comparative effectiveness study. (4th May 2022) - Urner, Martin; Barnett, Adrian G; Bassi, Gianluigi Li; Brodie, Daniel; Dalton, Heidi J; Ferguson, Niall D; Heinsar, Silver; Hodgson, Carol L; Peek, Giles; Shekar, Kiran; Suen, Jacky Y; Fraser, John F; et al.
Abstract: Objective: To estimate the effect of extracorporeal membrane oxygenation (ECMO) compared with conventional mechanical ventilation on outcomes of patients with covid-19 associated respiratory failure. Design: Observational study. Setting: 30 countries across five continents, 3 January 2020 to 29 August 2021. Participants: 7345 adults admitted to the intensive care unit with clinically suspected or laboratory confirmed SARS-CoV-2 infection. Interventions: ECMO in patients with a partial pressure of arterial oxygen to fraction of inspired oxygen (PaO2 /FiO2 ) ratio <80 mm Hg compared with conventional mechanical ventilation without ECMO. Main outcome measure: The primary outcome was hospital mortality within 60 days of admission to the intensive care unit. Adherence adjusted estimates were calculated using marginal structural models with inverse probability weighting, accounting for competing events and for baseline and time varying confounding. Results: 844 of 7345 eligible patients (11.5%) received ECMO at any time point during follow-up. Adherence adjusted mortality was 26.0% (95% confidence interval 24.5% to 27.5%) for a treatment strategy that included ECMO if the PaO2 /FiO2 ratio decreased <80 mm Hg compared with 33.2% (31.8% to 34.6%) had patients received conventional treatment without ECMO (risk difference –7.1%, 95% confidence interval –8.2% to –6.1%; risk ratio 0.78, 95% confidence interval 0.75 to 0.82). In secondary analyses, ECMO was most effective in patients aged <65 years and with a PaO2 /FiO2 <80 mm Hg or with driving pressures >15 cmH2 O during the first 10 days of mechanical ventilation. Conclusions: ECMO was associated with a reduction in mortality in selected adults with covid-19 associated respiratory failure. Age, severity of hypoxaemia, and duration and intensity of mechanical ventilation were found to be modifiers of treatment effectiveness and should be considered when deciding to initiate ECMO in patients with covid-19.